2022
DOI: 10.3389/fnagi.2022.873929
|View full text |Cite
|
Sign up to set email alerts
|

Dihuang-Yinzi Alleviates Cognition Deficits via Targeting Energy-Related Metabolism in an Alzheimer Mouse Model as Demonstrated by Integration of Metabolomics and Network Pharmacology

Abstract: Energy metabolism disturbance and the consequent reactive oxygen species (ROS) overproduction play a key and pathogenic role in the onset and progression of Alzheimer’s disease (AD). Dihuang-Yinzi (DHYZ) is a traditional Chinese herbal prescription clinically applied to treat AD and other neurodegenerative diseases for a long time. However, the systematical metabolic mechanism of DHYZ against AD remains largely unclear. Here we aimed to explore the mechanism of DHYZ in the treatment of AD comprehensively in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…The researchers conducted urinary metabolomics analysis of AD mice using UPLC-HRMS and identi ed that Rehmannia drink in uences four energy-related metabolic pathways, comprising glycerophospholipid metabolism, niacin/nicotinamide metabolism, glycation, and tricarboxylic acid cycle. They demonstrated that the disorder in glycerophospholipid metabolism is ameliorated by Rehmannia drink (Han et al 2022). The results of this study demonstrate that both Western medicine and traditional Chinese medicine have the potential to alleviate cognitive dysfunction in AD.…”
Section: Discussionmentioning
confidence: 53%
“…The researchers conducted urinary metabolomics analysis of AD mice using UPLC-HRMS and identi ed that Rehmannia drink in uences four energy-related metabolic pathways, comprising glycerophospholipid metabolism, niacin/nicotinamide metabolism, glycation, and tricarboxylic acid cycle. They demonstrated that the disorder in glycerophospholipid metabolism is ameliorated by Rehmannia drink (Han et al 2022). The results of this study demonstrate that both Western medicine and traditional Chinese medicine have the potential to alleviate cognitive dysfunction in AD.…”
Section: Discussionmentioning
confidence: 53%
“…Lei et al systematically investigated the antidepressant effects of paeoniflorin on CUMS rats based on a combination of LC-MS metabolomics and network pharmacology analysis, and identified the citrate cycle as an important metabolic pathway, and SLC6A4, TNF, IL6, and SLC6A3 as key targets ( Lei et al, 2022 ). Han et al analyzed the urine of a mouse model of Alzheimer’s disease for metabolomics and combined it with network pharmacology, and found that Dihuang-Yinzi improved four energy-related metabolic pathways to alleviate cognitive deficits in AD disease, including glycerophospholipid metabolism, niacin/nicotinamide metabolism, glycolysis and the tricarboxylic acid cycle ( Han et al, 2022 ). Therefore, our study integrated network pharmacology and metabolomics and provided a new research strategy for the antidepressant effect of XYS.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional Chinese herbal prescription Dihuang-Yinzi has long been used to treat neurodegenerative diseases such as AD. Investigation into its mechanism of action revealed that the ability to increase NAD content and enhance energy metabolism may contribute to its neuroprotective activity [ 153 ].…”
Section: Boosting Nad By Increasing Nad Synthesismentioning
confidence: 99%